Analisis Rule Kualitas Ayam Petelur Menggunakan Metode Simple Additive Weighting - Yuyun Yusnida Lase (RJOCS (Riau Journal of Computer Science), 2018)
Decision-making is the process of selecting alternative actions to achieve a certain goal or goal. Decision-making is done with a systematic approach to the problem through the process of collecting data into information and coupled with the factors that need to be considered in decision making. In the decision-making process, decision makers are often exposed to various criteria, such as chicken farmers, who often face difficulty in determining priorities in decision-making processes and policies regarding the quality of laying hens. This is influenced by the number of criteria determined in determining the quality of chicken eggs age, weight, nutritional food, environmental temperature and disease. In connection with this, the authors conducted a process of rules analysis to determine the quality of laying hens with Simple Additive weighting method (SAW). The process of analysis of the rules with Simple Additive Weighting (SAW) method is done by finding the weight of value for each attribute, then conducted a ranking process that will determine the optimal alternative in determining the quality of laying hens based on the criteria used, by Using this method will be able to produce chicken laying eggs where the egg quality is good.